PARTISIPASI SISWA SEKOLAH DASAR DALAM PENGELOLAAN SAMPAH - Ayuningsih, Hesti Fitri (HIGEIA (Journal of Public Health Research and Development), 2023)
Abstract Student participation at school in waste management is an effort to support waste reduction at the source. Waste management at Jatipuro 1 Public Elementary School is still not good, the students are still littering, and there is still trash scattered around. This is because student participation in waste management is still lacking. The research design uses a cross sectional design, the sampling technique uses simple random sampling. This research was conducted at Jatipuro 1 Public Elementary School in October 2022. The research data was obtained using a questionnaire with a population of 160 students and a total sample of 60 students was obtained using the Lemeshow formula. The results of the data used are primary data with data collection methods in the form of observation and interviews with questionnaire instruments. Data were analyzed using the Chi Square test to determine factors related to student participation in waste management. The results of the hypothesis test show that there is a relationship between knowledge (p value 0.000) and attitude (p value 0.011) with student participation in waste management. It is hoped that the school can continue to educate students to further increase their knowledge and attitudes to actively participate in waste management at school.